2021
DOI: 10.1039/d0gc04092d
|View full text |Cite
|
Sign up to set email alerts
|

A review on key design and operational parameters to optimize and develop hydrothermal liquefaction of biomass for biorefinery applications

Abstract: An increase in environmental awareness has resulted in a significant shift in research towards more renewable and sustainable energy sources and better waste valorization technologies. Within this vast field, biomass...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(92 citation statements)
references
References 334 publications
3
87
2
Order By: Relevance
“…Lignocellulosic biomass and macroalgae are mainly composed of carbohydrates (typically 40-50% and 55-60%, respectively), while microalgae primarily consist of protein (30-60%) or carbohydrates (20-40%) (Basar et al, 2021). The diverse compositions of MS could lead to complex reaction pathways in HTP and the MS-derived hydrochar with abundant functionalities.…”
Section: ==========================mentioning
confidence: 99%
See 2 more Smart Citations
“…Lignocellulosic biomass and macroalgae are mainly composed of carbohydrates (typically 40-50% and 55-60%, respectively), while microalgae primarily consist of protein (30-60%) or carbohydrates (20-40%) (Basar et al, 2021). The diverse compositions of MS could lead to complex reaction pathways in HTP and the MS-derived hydrochar with abundant functionalities.…”
Section: ==========================mentioning
confidence: 99%
“…However, it is suggested that these reaction pathways occur simultaneously during the HTP of MS. Detailed descriptions of each reaction mechanism can be found in our previous literature review (Basar et al, 2021) and elsewhere (He et al, 2014a;Wang et al, 2019a;. Indeed, diverse products formed through different pathways can largely affect the properties of hydrochar.…”
Section: Formation Pathways To Hydrocharmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that although increasing aqueous temperature from 30 to 70 • C could slightly (<1%) enhance P extraction efficiency, it leached more metals (e.g., Ca, Cu, Fe, and Mn) from ash by 0.05 M H 2 SO 4 at an L/S ratio of 150 mL/g for 4 h. It was determined that elevated temperature was not suitable for P extraction as it caused high solubility of metals [117]. Semerci et al also compared the impacts of extraction temperature (23,30, and 70 • C) and found that temperature was neither effective nor economical on P extraction [114]. Most other studies only investigated acidic extraction under room temperature (20-25 • C) and atmospheric pressure.…”
Section: Influential Factors For P Extractionmentioning
confidence: 99%
“…Third, compared to high incineration temperatures (e.g., 900 • C), reaction temperatures of HTL are much lower and thus decrease the risk of reactor corrosion. Based on our previous literature review [30], the current state of HTL systems is still at pilot-scale requiring further demonstrations, and thus studies related to HTL process will continue to be popular in the next decades. With the ever-increasing stress of depleting fossil fuel and resources (particularly P), building an energy and P recovery system (i.e., coupling HTL and P recovery) is a crucial and sustainable approach.…”
Section: Introductionmentioning
confidence: 99%